Aggressive CD4-CD8-CD45RA+CCR10- Primary Cutaneous Peripheral T-cell Lymphoma, Not Otherwise Specified: A Case Report - Natsumi Ikumi; Hideki Fujita; Tadashi Terui; Hiromichi Takahashi; Katsuhiro Miura; Yoshihiro Hatta; Masami Takei (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)